Recurrent extensive plunging ranula: A rare case - Ali R AlHayek; Manahel A Almulhem; Mohammed A Alhashim; Nasser A Aljazan (Wolters Kluwer Medknow Publications, 2018)
Plunging ranula (PR) is a cystic mass presenting on the lateral side of the neck with or without a history of the usual presentation of an intraoral lesion. "PR" is recognized as an uncommon lesion that has been found predominantly in the third decade of life mostly in males. However, the exact prevalence of "PR" is not yet known. We report a rare case of an extensive PR that reached the parapharyngeal space in a 17-year-old Saudi female. The diagnosis was made when she presented to the ENT clinic with swellings in the right submandibular and right floor of the mouth. The diagnosis of "PR" with the absence of an oral lesion is very challenging and requires a detailed history, clinical examination, and radiological imaging. Different modalities of treatment have been discussed. However, the excision of ranula and the sublingual gland is the most effective way of management.